Analysis of Sragen Regency Regional Regulation Number 3 of 2018 Concerning Control and Supervision of Alcoholic Drinks Circulation - Wantara; Vicki Dwi Purnomo; Syukron Abdul Kadir; Benedictus Hestu Cipto Handoyo (PT FORMOSA CENDEKIA GLOBAL, 2023)
Law Number 23 of 2014 concerning Regional Government, as also stipulated in Government Regulation of the Republic of Indonesia Number 16 of 2016 concerning Civil Service Police Units stipulates that the Civil Service Police Unit is formed to enforce Regional Regulations, administer public order and public order, and provide protection Public. The Civil Service Police Unit as a regional apparatus, has a very strategic role in ensuring legal certainty. In Sragen Regency there are many sales and circulation of alcoholic drinks, even though in Sragen Regency there is a regional regulation (Perda) which regulates the prohibition of the sale, distribution and use of alcoholic drinks with the existence of Regional Regulation of Sragen Regency Number 3 of 2018 concerning Control and Supervision of Distribution of Alcoholic Beverages . It is an effort to take action against business actors and the circulation of alcoholic beverages in Sragen Regency.